Nasal soft-tissue and vault deviation in unicoronal synostosis. Issue 5 (May 2015) - Silveira Camargos, Isadora; Metzler, Philipp; Persing, John; Alcon, Andre; Steinbacher, Derek M.
Summary Background Unicoronal synostosis (UCS) results in nasal root deviation toward the fused side of the face, resulting in an apparent nasal dorsal deviation to the non-fused side. The impact of the altered radix position on the osteocartilaginous vault and nasal soft tissue has not been analyzed. The purpose of this study is to morphometrically assess the nasal structure and deviation in UCS. We hypothesize the proximal etiology exerts an impact on the distal nasal form, compared to controls. Methods Demographic data were tabulated and computed tomographic information recorded. Three-dimensional reconstruction was created and analyzed digitally (using Surgi Case). Morphometric landmarks were determined and used to perform measurements on the nasal soft tissue and osseous skull surface to evaluate nasal deviation within a midsaggital plane (MSP). Results Forty three-dimensional CT scans of 20 UCS patients and 20 control subjects were analyzed. The deviation angle of the nose to the non-fused side was 6.6 ± 2.9° in the bony layer. In the soft-tissue layer, the deviation angle of the nasal dorsum line to the non-fused side was 5.4 ± 3.4°. The tip of the nose showed a significant deviation to the non-fused side (2.2 ± 1.2 mm). Paired landmarks (alares, inferior lateral nostril bases) related to the MSP showed a greater distance on the non-fused side. Paired landmarks related to an intrinsic nasal midline (Nsup-ANS; tip-columella line (TCL)) did not show any significant differences. Conclusion UCS confers osteocartilaginous and soft-tissue nasal deviation, with the distal nose toward the non-fused side. The nasal root inclination underpins this asymmetry across the midsaggital reference plane. However, the nose in isolation exhibits balanced side–side proportions.